An investigation of 8-hydroxy-2’-deoxyguanosine and 8-isoprostaglandin F2α levels in patients with larynx carcinoma - Said Çetin, Yaser; Düzenli, Ufuk; Berköz, Mehmet; Özkan, Hüseyin; Bozan, Nazım (ENT Updates, 2020)
Objective: 8-hydroxy-2’-deoxyguanosine (8-OHdG) and 8-iso-prostaglandin F2α (8-iso-PGF2α) are indicators of oxidative stress in the human body. The aim of the present study was to investigate serum 8-OHdG and 8-iso-PGF2α levels in patients with larynx carcinoma and to compare them with healthy controls. Methods: A total of 50 patients, consisting of 25 patients with larynx carcinoma (study group) and 25 healthy subjects (control group), were enrolled in the present study. Serum 8-OHdG concentration was measured using an ELISA kit, whereas an enzyme immunoassay kit was utilized for the measurement of serum 8-iso-PGF2α levels. TNM stages of the patients were recorded from the patient records in the study group. Results: 8-OHdG and 8-iso-PGF2α levels were significantly higher in patients with larynx carcinoma than the control subjects. 8-OHdG levels were significantly higher in patients with LN metastases than the patients without LN metastases in the study group. Conclusion: The findings of the present study showed the presence of significantly increased serum 8-OHdG and 8-iso-PGF2α levels in patients with larynx carcinoma, which may support the role of oxidative stress in the development laryngeal cancers.